EVALUASI SISTEM PENYALIRAN TAMBANG BATUBARA PT. RIMAU ENERGY MINING SITE PUTUT TAWULUH KECAMATAN DUSUN TIMUR KABUPATEN BARITO TIMUR PROVINSI KALIMANTAN TENGAH - Widyantoro, Wisnu; Marsud, -; Syafrianto, M. Khalid (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2020)
PT. Rimau Energy Mining is an open-pit coal mine located in East Barito, Central Kalimantan Province. Mining activities depend on the weather conditions of the mine site include rain. Water disrupting the mining work area is then transferred to the water reservoir in block 14, which is the direction of the mine's progress towards the block. The research method used is direct field observation and direct calculation, the method used is collecting rainfall data, calculating the catchment area using the Auto CAD 2007 application, calculating the volume of water in the water reservoir, calculating the actual pump discharge. Calculations on PIT 1 produce rainfall intensity for 3 hours amounting to 7,319 mm / hour resulting in runoff discharge of 4,678 mmÂ³ / hour. TheÂ  pumping system in pit 1 used 3 pumps, 1 unit KSB DND 15 in block 12 and in block 14 using 2 unit sykes pumps HH160i and sykes HH220i. Draining the reservoir water in block 14 with a target planning time of 3.5 months by using available pumps, by optimizing the performance of the existing pump,within3.5monthscanremovetheexistingwaterinthereservoirinblock14totheelevation-5.5 m from the initial elevation of 3.9 m using a pump rotation speed of 1600 RPM.Key Word : Pump, Rainfall, Water reservoir